Is the much discussed agility of corporate real estate visible in practice? An empirical study of the relationship between business metrics and surplus property - Cooke, Howard; Appel-Meulenbroek, Rianne; Arentze, Theo (International Journal of Strategic Property Management, 2019)
Very little work has been undertaken on the consequences of economic recession on Corporate Real Estate (CRE) and its realignment following strategy changes. Only those CRE portfolios with short term leases have a dynamic alignment capability allowing them to readily adjust to change. For those with longer leases this leads to the creation of a surplus property provision (SPP). This paper analyses the relationship between SPP and metrics for business and CRE through a period of significant change, by examining company annual reports using a distributed time lag auto-regression model. The results show an inverse relationship between SPP and profits but a positive relationship with both turnover and employment, suggesting that declining profits trigger the re-shaping of CRE. SPP is used to provide portfolio flexibility because of the lack of dynamic alignment capability. SPP increases as the commitment to short leases (